Two birds with one stone: human SIRPα nanobodies for functional modulation and in vivo imaging of myeloid cells - Wagner, Teresa R.; Blaess, Simone; Leske, Inga B.; Frecot, Desiree I.; Gramlich, Marius; Traenkle, Bjoern; Kaiser, Philipp D.; Seyfried, Dominik; Maier, Sandra; Rezza, Amélie; Sônego, Fabiane; Thiam, Kader; et al. (Frontiers in Immunology, 2023)
Signal-regulatory protein α (SIRPα) expressed by myeloid cells is of particular interest for therapeutic strategies targeting the interaction between SIRPα and the "don't eat me" ligand CD47 and as a marker to monitor macrophage infiltration into tumor lesions. To address both approaches, we developed a set of novel human SIRPα (hSIRPα) -specific nanobodies (Nbs). We identified high-affinity Nbs targeting the hSIRPα/hCD47 interface, thereby enhancing antibody-dependent cellular phagocytosis (ADCP). For non-invasive in vivo imaging, we chose S36 Nb as a non-modulating binder. By quantitative positron emission tomography (PET) in novel hSIRPα/hCD47 knock-in (KI) mice, we demonstrated the applicability of 64Cu-hSIRPα-S36 Nb to visualize tumor infiltration of myeloid cells. We envision that the hSIRPα-Nbs presented in this study have potential as versatile theranostic probes, including novel myeloid-specific checkpoint inhibitors for combinatorial treatment approaches and for in vivo stratification and monitoring of individual responses during cancer immunotherapies.